Quality changes and storage life of common carp (Cyprinus carpio) with the use of Ginger (Zingiber officinale) essential oil: The Use of Essential Oil İn Food Preservation - Erecevit Sönmez, Pinar; Karaton Kuzgun, Nermin; Kırbağ , Sevda (Progress in Nutrition, 2021)
Ginger (Zingiber officinale) essential oil is considered safe. In this study, ginger (Zingiber officinale) essential oil was used to extend storage life of common carp (Cyprinus carpio) and detect its protective effects.The following tests were performed to assess the shelf life of carp (C:control) treated with ginger essential oil (G). The microbiota growth of the carp, sensory properties, pH, TVB TBA values, the shelf life of the carp changed positively by adding ginger oil in different concentrations to the carp (C1, C2, C3: 0.1%, 0.25%, 0.5%ginger essential oil was added to carp samples).On the other hand; ginger essential oil has a positive effect on TVB-N and TBA values of carp fillets. With reference to the results of microbiota growth, carp sample (C: control) showed the highest value (P < 0.05) on the 6th storage day.The results show the importance of the use of Zingiber officinale essential oil to prevent food spoilage.